THE RELATIONSHIP BETWEEN SCIENCE AND DEMOCRACY ON PHILIP KITCHER’S PERSPECTIVES - Moch Zihad Islami; Lailiy Muthmainnah (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2023)
The relationship between science and democracy has been an interesting and important issue in the study of philosophy as well as political science. Democracy does not only apply in the political realm but can also be seen in the context of science. This paper uses a political-philosophical approach to explore the relationship between science and democracy from the perspective of Philip Kitcher. As far as the philosophical research model used in this research is the concept of figure thinking by using primary sources in the form of Philip Kitcher's two main works among other works, namely: Kitcher's Science, Truth, and Democracy (2001) and Science in a Democratic Society (2011), as well as secondary sources such as books, journal articles and sources relevant to the concepts of the relationship between science and democracy. This paper concludes that the relationship between science and democracy according to Kitcher is based on the concept of a partnership model. This model emphasizes that scientists should consider how knowledge can be applied in a social and practical context, as well as enabling the active participation of the public democratically in the process of scientific research. The relationship between science and democracy, according to Kitcher, relates to the epistemological and socio-practical significance to be taken into account in scientific decision-making, as well as taking into account the public perspective in decision-making. In Kitcher’s perspective too, integration between science and democracy became essential to forming a normative framework for more transparent, democratic scientific research, and producing high-quality knowledge.